Cultivating a landscape of learning: a rural educational and community node in the Breërivier Valley - Droomer, Mieke (School of Architecture, Planning and Geomatics, 2016)
This thesis confronts the spatiality of farm worker communities in the Breërivier, in an attempt to find a programmatic intervention that will create collective community space. It thus turns to its context, the landscape and the farming that embraces the site as a generator of form and language. In essential, the thesis is hoping to find a new critical "vernacular" that responds to the ruralscape.